Method for preparing benzyl alcohol through benzaldehyde hydrogenation by using Au-coated Pt / C catalyst

By using the AU@PT catalyst, load to the activated carbon, the problem of low selectiveness and high energy consumption when catalyzed benzaldehyde derivation in existing technologies, and realized high -efficiency benzenedehydedexed and high -selective benzinylene preparation. It has the advantages of environmental protection and economy.

CN119346105AActive Publication Date: 2025-01-24NANJING TECH UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411645811.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-24
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

In the prior art, when catalyzing benzaldehyde hydrogenation to prepare benzal alcohol, there are problems of low selectivity and high energy consumption, especially when Pt nanoparticle catalysts generate more deep hydrogenation product toluene in the reaction.

Method used

Using Au@Pt catalyst, a 1wt% Au@Pt/C catalyst was prepared by combining Au nanoparticles with Pt nanoparticles and loading them on activated carbon, which was used to catalyze the hydrogenation reaction of benzaldehyde under mild conditions.

Benefits of technology

The high conversion rate of benzaldehyde and the high selectivity of benzislerol. Compared with the PT -based catalyst, the yield rate of benzinol alcohol has increased by more than 45%, and the catalyst has high activity and stability. Energy consumption is more friendly to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346105A_ABST
    Figure CN119346105A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing benzyl alcohol through benzaldehyde hydrogenation by using an Au-coated Pt / C catalyst. According to the reaction, benzaldehyde is used as a raw material, a supported Au core-Pt shell nanostructure catalyst is used for catalyzing conversion of benzaldehyde, one-pot hydrogenation of benzaldehyde is carried out in an isopropanol solvent under the conditions of 1 wt% of hydrogen and 60 DEG C by using a 1 wt% Au at Pt / C (mAu: mPt = 1: 1.22) catalyst, the conversion rate of benzaldehyde is 99.9%, the selectivity of benzyl alcohol is 96.9%, and the yield of benzyl alcohol is increased by more than 45% compared with that of a Pt-based catalyst. The catalyst is better than most reported catalysts at present. The preparation process of the catalyst is simple, the catalyst has high activity and stability, the reaction conditions are milder, the energy consumption is reduced to a certain extent, and the catalyst is more environment-friendly. Therefore, the method has a wide application prospect in the industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomass energy catalysis, and relates to a method for catalyzing the hydrogenation of biomass derivative benzaldehyde to prepare fine chemical benzyl alcohol, and in particular to a catalyst with an Au core Pt shell nanostructure, which can effectively catalyze the selective hydrogenation of benzaldehyde to prepare benzyl alcohol. Background Art

[0002] In the energy and chemical industries, fossil carbon sources are increasingly being replaced by renewable carbonaceous materials to reduce greenhouse gas carbon dioxide emissions and thus mitigate global warming. Forest biomass lignin is an abundant and renewable carbon resource that has the potential to replace traditional non-renewable fossil resources in the production of chemicals and fuels. Lignin is derived from lignocellulosic biomass, which can be depolymerized into various platform compounds that can be further upgraded to high-value chemicals and fuels.

[0003] Benzaldehyde is an important biomass-based platform compound. It is an important chemical intermediate and is commonly used as a solvent for inks, paints and varnishes. It is also an indispensable fixative for the formulation of cosmetics and some fine chemical products (such as flavors). It was originally commercially synthesized by hydrolysis of benzyl chloride and sodium hydroxide, but the hydrolysis process leaves excess chlorine residues in the product, causing serious environmental toxicity. In addition, it can also be prepared by electrochemical hydrogenation of benzaldehyde, electrochemical oxidation of toluene and liquid-phase catalytic hydrogenation of benzaldehyde. Among these methods, liquid-phase catalytic hydrogenation of benzaldehyde is a better choice because of its advantages such as low energy consumption and simple process, which has attracted widespread attention from researchers. Pt-based catalysts have been relatively studied in catalytic benzaldehyde hydrogenation due to their high catalytic activity. Catalysts based on Pt nanoparticles often produce more deep hydrogenation products such as toluene during benzaldehyde hydrogenation. Doping and modifying Pt-based catalysts to make them have higher benzyl alcohol selectivity is one of the effective means to solve this problem. In view of the above problems, it is imperative to develop new strategies and methods for preparing catalysts to improve conversion efficiency and selectivity of target products. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a method for preparing benzyl alcohol by hydrogenating benzaldehyde using Au@Pt catalyst. The preparation process of the present invention is simple, the catalyst has high activity and stability, the reaction conditions are milder, the energy consumption is reduced to a certain extent, and it is more environmentally friendly. The present invention has broad application prospects in industry.

[0005] The 1wt% Au@Pt / C (m Au :m Pt=1:1.22) catalyst, which can achieve high conversion of benzaldehyde and high selectivity of benzyl alcohol under mild conditions.

[0006] In order to solve the technical problem of the present invention, a technical solution is proposed: a method for preparing benzyl alcohol by hydrogenating benzaldehyde using Au@Pt catalyst, comprising the following steps:

[0007] (1) mixing a chloroauric acid solution with a sodium citrate aqueous solution and reducing it with a sodium borohydride aqueous solution to obtain Au nanoparticles;

[0008] (2) mixing the chloroplatinic acid solution with the Au nanoparticles in step (1), and reducing them with ascorbic acid to obtain Au@Pt nanoparticles; wherein the mass ratio of the two metals Au:Pt is 1:1.22;

[0009] (3) Adding activated carbon into deionized water and dispersing by stirring, and then subjecting to ultrasound to obtain activated carbon slurry;

[0010] (4) Using activated carbon as a carrier, the activated carbon slurry in step (3) is mixed with the Au@Pt nanoparticles in step (2), and the obtained suspension is filtered and dried to prepare an Au@Pt / C catalyst; wherein the total mass fraction of Au and Pt metals accounts for 1wt% of the catalyst;

[0011] (5) Adding the reaction raw materials benzaldehyde, solvent and the Au@Pt / C catalyst of step (4) into a high-pressure reactor equipped with a thermal conductivity detector, and hydrogenating benzaldehyde to prepare benzyl alcohol under stirring; the initial hydrogen pressure is 1-2 MPa; the reaction temperature is 40-100°C; the reaction time is ≥2 h; the solvent is isopropanol; after the reaction, the catalyst and the reaction liquid are separated by centrifugation.

[0012] Preferably, in step (5), the catalyst is used in a molar ratio of Pt to benzaldehyde of 1:1000.

[0013] Preferably, (1) Preparation of Au nanoparticles: 150 mL of deionized water is measured and placed in a beaker, a certain amount of Au precursor salt chloroauric acid is added to the beaker, an appropriate amount of sodium citrate is weighed and added to the beaker, and stirred at 1200 rpm for 1 min; a certain amount of sodium borohydride is weighed and dissolved in 10 mL of ice deionized water, and the prepared sodium borohydride solution is quickly added to the vigorously stirred Au precursor with a 5 mL plastic dropper, the solution quickly changes from light yellow to wine red, and the solution is stirred at 1200 rpm for 5 minutes, then the stirring is turned off, and the solution is left to stand at room temperature for 1 h. The prepared Au nanoparticles are stored in a refrigerator at 4°C;

[0014] (2) Preparation of Au@Pt nanoparticles: The Au nanoparticle aqueous solution prepared in step (1) was stirred at 1200 rpm; a certain amount of Pt precursor salt chloroplatinic acid was added and stirred for 1 min; a certain amount of ascorbic acid was weighed and dissolved in 10 mL of deionized water, and the prepared ascorbic acid solution was added to a beaker using a 5 mL plastic dropper, and stirred at 1200 rpm for 45 min to obtain an Au@Pt nanoparticle aqueous solution. The prepared Au@Pt nanoparticles were stored in a refrigerator at 4°C.

[0015] (3) Take a certain amount of activated carbon in a beaker, add 300 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain activated carbon slurry;

[0016] (4) Loading Au@Pt onto activated carbon: Stir the activated carbon slurry prepared in step (3) at 1200 rpm, add the Au@Pt nanoparticle solution prepared in step (2) dropwise into the activated carbon slurry using a 5 mL plastic dropper, and stir for 1 h.

[0017] (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after the filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After the drying was completed, the dish was sealed and stored;

[0018] (6) Add the reaction materials, solvent and catalyst into a high-pressure reactor equipped with a thermal conductivity detector, and carry out catalytic hydrogenolysis reaction under stirring; before the reaction, purge the reactor with hydrogen several times to remove the air in the reactor.

[0019] Preferably, the catalyst is prepared by the following steps:

[0020] (1) Preparation of Au nanoparticles: Measure 150 mL of deionized water and place it in a beaker. Take 1 g of HAuCl4 and dissolve it in 25 mL of deionized water to prepare an Au precursor solution with Au: 18.335 mg / mL for later use. Take 491 μL of the Au precursor solution and add it to a beaker. Take an appropriate amount of sodium citrate with a mass ratio of Au to sodium citrate of 1:5 and add it to the beaker. Stir at 1200 rpm for 1 min. Weigh 7.5 mg of sodium borohydride and dissolve it in 10 mL of ice deionized water. Use a 5 mL plastic dropper to quickly add the prepared sodium borohydride solution to the vigorously stirred Au precursor. The solution quickly changes from light yellow to wine red. Stir at 1200 rpm for 5 minutes and then turn off the stirring. Let it stand at room temperature for 1 h. The prepared Au nanoparticles are stored in a refrigerator at 4°C.

[0021] (2) Preparation of Au@Pt nanoparticles: The Au nanoparticle aqueous solution prepared in step (1) was stirred at 1200 rpm, 1 g of H2PtCl6 was dissolved in 50 mL of deionized water to prepare a Pt precursor solution, Pt: 7.61 mg / mL for later use; 1445 μL of the Pt precursor solution was added to the Au nanoparticle aqueous solution and stirred for 1 min; 20 mg of ascorbic acid was weighed and dissolved in 10 mL of deionized water, and the prepared ascorbic acid solution was added to a beaker using a 5 mL plastic dropper, and stirred at 1200 rpm for 45 min to obtain an Au@Pt nanoparticle aqueous solution. The prepared Au@Pt nanoparticles were stored in a refrigerator at 4°C.

[0022] (3) Take 1980 mg of activated carbon in a beaker, add 300 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain activated carbon slurry;

[0023] (4) Loading Au@Pt onto activated carbon: Stir the activated carbon slurry prepared in step (3) at 1200 rpm, add the Au@Pt nanoparticle solution prepared in step (2) dropwise into the activated carbon slurry using a 5 mL plastic dropper, and stir for 1 h.

[0024] (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After drying, the dish was sealed and stored. The catalyst was 1wt% Au@Pt / C m Au :m Pt =1:1.22.

[0025] Preferably, the reaction conditions in step (5) are as follows: an initial hydrogen pressure of 1 MPa, a reaction temperature of 60° C., and a reaction time of 2 h.

[0026] Preferably, in step (5), the mass of the catalyst added to the reactor is 1 mmol benzaldehyde and 10 mL isopropanol in a molar ratio of Pt to benzaldehyde of 1:1000.

[0027] Preferably, using 1wt% Au@Pt / C m Au :m Pt =1:1.22 catalyzes the hydrogenation of benzaldehyde to prepare benzyl alcohol. The reaction is carried out at 1 MPa hydrogen pressure and 60°C for 120 min. The benzaldehyde conversion rate is 99.9% and the benzyl alcohol selectivity is 96.9%.

[0028] Beneficial effects:

[0029] The present invention provides a method for preparing an Au core-Pt shell nanostructured catalyst. The 1wt% Au@Pt / C (m Au :m Pt =1:1.22) catalyst, which can achieve high benzaldehyde conversion and high benzyl alcohol selectivity under mild conditions. Under 1 MPa hydrogen and 60 ° C, benzaldehyde was hydrogenated in isopropanol solvent in one pot, with a benzaldehyde conversion of 99.9% and a benzyl alcohol selectivity of 96.9%. The benzyl alcohol yield was increased by more than 45% compared with Pt-based catalysts, which is better than most of the catalysts reported so far.

[0030] The catalyst prepared in Example 1 1wt% Au@Pt / C (m Au :m Pt =1:0.54) benzaldehyde conversion rate was 89.9%, benzyl alcohol selectivity was 94.1%; the catalyst Au@Pt / C (m Au :m Pt =1:2.07) benzaldehyde conversion rate was 97.4%, benzyl alcohol selectivity was 96.2%; the catalyst Au@Pt / C (m Au :m Pt =1:3) benzaldehyde conversion rate was 98.7%, benzyl alcohol selectivity was 87.6%; the catalyst Au@Pt / C (m Au :m Pt =1:1.22) benzaldehyde conversion rate is 99.9%, benzyl alcohol selectivity is 96.9%, catalytic performance is the best among the catalysts prepared in Examples 1-4, and compared with Pt / C prepared by impregnation method, benzyl alcohol yield is improved by more than 45%. In addition, the activity and selectivity of the catalyst with Au core Pt shell structure are better than those of Pt / C catalyst and Au-Pt / C catalyst with alloy structure.

[0031] As can be seen from Table 2, the catalyst with activated carbon as the carrier has a benzaldehyde conversion rate of 99.9% and a benzyl alcohol selectivity of 96.9%, which is the best.

[0032] The present invention prepares a series of supported Au core-Pt shell nanostructured catalysts and applies them to the reaction of preparing benzyl alcohol by hydrogenation of benzaldehyde. By optimizing the reaction conditions, it is found that the optimized 1wt% Au@Pt / C (m Au :m Pt=1:1.22), isopropanol as solvent, under the reaction conditions of 1 MPa hydrogen pressure and 60°C, the reaction time is 120 min, and a 99.9% conversion rate of benzaldehyde and a 96.9% selectivity of benzyl alcohol can be achieved. The results of the catalyst cycle reaction show that after 5 consecutive cycles, the benzaldehyde conversion rate decreased slightly from 99.9% to 94.4%, while the benzyl alcohol yield was still 90.0%. This shows that 1wt% Au@Pt / C (m Au :m Pt =1:1.22) The catalyst has good reusability. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 TEM and EDS images of the Au@Pt / C catalyst prepared in Example 2. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below in conjunction with specific examples. These embodiments are only for illustrating the present invention, but the present invention is not limited to the following embodiments.

[0035] Example 1

[0036] (1) Preparation of Au nanoparticles. Measure 150 mL of deionized water and place it in a beaker. The precursor of Au can be its metal precursor salt solution. Taking chloroauric acid as an example, take 1 g of HAuCl4 and dissolve it in 25 mL of deionized water to prepare an Au precursor solution (Au: 18.335 mg / mL) for later use. Take 709 μL of the Au precursor solution and add it to the beaker. Measure an appropriate amount of sodium citrate (the mass ratio of Au to sodium citrate is 1:5) and add it to the beaker. Stir at 1200 rpm for 1 min. Weigh 10.8 mg of sodium borohydride and dissolve it in 10 mL of ice deionized water. Use a 5 mL plastic dropper to quickly add the prepared sodium borohydride solution to the vigorously stirred Au precursor. The solution quickly changes from light yellow to wine red. Stir at 1200 rpm for 5 minutes and then turn off the stirring. Let it stand at room temperature for 1 hour. The prepared Au nanoparticles can be stored in a refrigerator at 4°C.

[0037] (2) Preparation of Au@Pt nanoparticles. The Au nanoparticle aqueous solution prepared in step (1) was stirred at 1200 rpm. The precursor of Pt can be its metal precursor salt solution. Taking chloroplatinic acid as an example, 1 g of H2PtCl6 was dissolved in 50 mL of deionized water to prepare a Pt precursor solution (Pt: 7.61 mg / mL) for later use. 920 μL of the Pt precursor solution was added to the Au nanoparticle aqueous solution and stirred for 1 min. 12.8 mg of ascorbic acid was weighed and dissolved in 10 mL of deionized water. A 5 mL plastic dropper was used to add the prepared ascorbic acid solution to a beaker and stirred at 1200 rpm for 45 min to obtain an Au@Pt nanoparticle aqueous solution. The prepared Au@Pt nanoparticles can be stored in a refrigerator at 4°C.

[0038] (3) Take 1980 mg of activated carbon in a beaker, add 300 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain activated carbon slurry.

[0039] (4) Loading Au@Pt onto activated carbon. The activated carbon slurry prepared in step (3) was stirred at 1200 rpm, and the Au@Pt nanoparticle solution prepared in step (2) was added dropwise to the activated carbon slurry using a 5 mL plastic dropper and stirred for 1 h.

[0040] (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after the filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After the drying, it was sealed and stored.

[0041] The catalyst was named 1wt%Au@Pt / C (m Au :m Pt =1:0.54).

[0042] Example 2

[0043] (1) Preparation of Au nanoparticles. Measure 150 mL of deionized water and place it in a beaker. The precursor of Au can be its metal precursor salt solution. Taking chloroauric acid as an example, take 1 g of HAuCl4 and dissolve it in 25 mL of deionized water to prepare an Au precursor solution (Au: 18.335 mg / mL) for later use. Take 491 μL of the Au precursor solution and add it to the beaker. Measure an appropriate amount of sodium citrate (the mass ratio of Au to sodium citrate is 1:5) and add it to the beaker. Stir at 1200 rpm for 1 min. Weigh 7.5 mg of sodium borohydride and dissolve it in 10 mL of ice deionized water. Use a 5 mL plastic dropper to quickly add the prepared sodium borohydride solution to the vigorously stirred Au precursor. The solution quickly changes from light yellow to wine red. Stir at 1200 rpm for 5 minutes and then turn off the stirring. Let it stand at room temperature for 1 hour. The prepared Au nanoparticles can be stored in a refrigerator at 4°C.

[0044] (2) Preparation of Au@Pt nanoparticles. The Au nanoparticle aqueous solution prepared in step (1) was stirred at 1200 rpm. The precursor of Pt can be its metal precursor salt solution. Taking chloroplatinic acid as an example, 1 g of H2PtCl6 was dissolved in 50 mL of deionized water to prepare a Pt precursor solution (Pt: 7.61 mg / mL) for later use. 1445 μL of the Pt precursor solution was added to the Au nanoparticle aqueous solution and stirred for 1 min. 20 mg of ascorbic acid was weighed and dissolved in 10 mL of deionized water. A 5 mL plastic dropper was used to add the prepared ascorbic acid solution to a beaker and stirred at 1200 rpm for 45 min to obtain an Au@Pt nanoparticle aqueous solution. The prepared Au@Pt nanoparticles can be stored in a refrigerator at 4°C.

[0045] (3) Take 1980 mg of activated carbon in a beaker, add 300 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain activated carbon slurry.

[0046] (4) Loading Au@Pt onto activated carbon. The activated carbon slurry prepared in step (3) was stirred at 1200 rpm, and the Au@Pt nanoparticle solution prepared in step (2) was added dropwise to the activated carbon slurry using a 5 mL plastic dropper and stirred for 1 h.

[0047] (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after the filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After the drying, it was sealed and stored.

[0048] The catalyst was named 1wt%Au@Pt / C (m Au :m Pt =1:1.22).

[0049] Example 3

[0050] (1) Preparation of Au nanoparticles. Measure 150 mL of deionized water and place it in a beaker. The precursor of Au can be its metal precursor salt solution. Taking chloroauric acid as an example, take 1 g of HAuCl4 and dissolve it in 25 mL of deionized water to prepare an Au precursor solution (Au: 18.335 mg / mL) for later use. Take 355 μL of the Au precursor solution and add it to the beaker. Measure an appropriate amount of sodium citrate (the mass ratio of Au to sodium citrate is 1:5) and add it to the beaker. Stir at 1200 rpm for 1 min. Weigh 5.5 mg of sodium borohydride and dissolve it in 10 mL of ice deionized water. Use a 5 mL plastic dropper to quickly add the prepared sodium borohydride solution to the vigorously stirred Au precursor. The solution quickly changes from light yellow to wine red. Stir at 1200 rpm for 5 minutes and then turn off the stirring. Let it stand at room temperature for 1 hour. The prepared Au nanoparticles can be stored in a refrigerator at 4°C.

[0051] (2) Preparation of Au@Pt nanoparticles. The aqueous solution of Au nanoparticles prepared in step (1) was stirred at 1200 rpm. The precursor of Pt can be its metal precursor salt solution. Taking chloroplatinic acid as an example, 1 g of H2PtCl6 was dissolved in 50 mL of deionized water to prepare Pt for use. 1774 μL of Pt precursor solution was added to the aqueous solution of Au nanoparticles and stirred for 1 min. 24.5 mg of ascorbic acid was weighed and dissolved in 10 mL of deionized water. A 5 mL plastic dropper was used to add the prepared ascorbic acid solution to a beaker and stirred at 1200 rpm for 45 min to obtain an aqueous solution of Au@Pt nanoparticles. The prepared Au@Pt nanoparticles can be stored in a refrigerator at 4°C.

[0052] (3) Take 1980 mg of activated carbon in a beaker, add 300 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain activated carbon slurry.

[0053] (4) Loading Au@Pt onto activated carbon. The activated carbon slurry prepared in step (3) was stirred at 1200 rpm, and the Au@Pt nanoparticle solution prepared in step (2) was added dropwise to the activated carbon slurry using a 5 mL plastic dropper and stirred for 1 h.

[0054] (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after the filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After the drying, it was sealed and stored.

[0055] The catalyst was named 1wt%Au@Pt / C (mAu :m Pt =1:2.07).

[0056] Example 4

[0057] (1) Preparation of Au nanoparticles. Measure 150 mL of deionized water and place it in a beaker. The precursor of Au can be its metal precursor salt solution. Taking chloroauric acid as an example, take 1 g of HAuCl4 and dissolve it in 25 mL of deionized water to prepare an Au precursor solution (Au: 18.335 mg / mL) for later use. Take 273 μL of the Au precursor solution and add it to the beaker. Measure an appropriate amount of sodium citrate (the mass ratio of Au to sodium citrate is 1:5) and add it to the beaker. Stir at 1200 rpm for 1 min. Weigh 4.2 mg of sodium borohydride and dissolve it in 10 mL of ice deionized water. Use a 5 mL plastic dropper to quickly add the prepared sodium borohydride solution to the vigorously stirred Au precursor. The solution quickly changes from light yellow to wine red. Stir at 1200 rpm for 5 minutes and then turn off the stirring. Let it stand at room temperature for 1 hour. The prepared Au nanoparticles can be stored in a refrigerator at 4°C.

[0058] (2) Preparation of Au@Pt nanoparticles. The aqueous solution of Au nanoparticles prepared in step (1) was stirred at 1200 rpm. The precursor of Pt can be its metal precursor salt solution. Taking chloroplatinic acid as an example, 1 g of H2PtCl6 was dissolved in 50 mL of deionized water to prepare Pt for use. 1971 μL of Pt precursor solution was added to the aqueous solution of Au nanoparticles and stirred for 1 min. 27.2 mg of ascorbic acid was weighed and dissolved in 10 mL of deionized water. A 5 mL plastic dropper was used to add the prepared ascorbic acid solution to a beaker and stirred at 1200 rpm for 45 min to obtain an aqueous solution of Au@Pt nanoparticles. The prepared Au@Pt nanoparticles can be stored in a refrigerator at 4°C.

[0059] (3) Take 1980 mg of activated carbon in a beaker, add 300 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain activated carbon slurry.

[0060] (4) Loading Au@Pt onto activated carbon. The activated carbon slurry prepared in step (3) was stirred at 1200 rpm, and the Au@Pt nanoparticle solution prepared in step (2) was added dropwise to the activated carbon slurry using a 5 mL plastic dropper and stirred for 1 h.

[0061] (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after the filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After the drying, it was sealed and stored.

[0062] The catalyst was named 1wt%Au@4 ML-Pt / C (m Au :m Pt =1:3).

[0063] Example 5

[0064] (1) The reaction of hydrogenating benzaldehyde to prepare benzyl alcohol was carried out in a high-pressure reactor equipped with a thermal conductivity detector. First, an appropriate amount of 1 wt% Au@Pt / C (m Au :m Pt =1:1.22) catalyst (the molar ratio of Pt to benzaldehyde in the catalyst is 1:1000), 1 mmoL benzaldehyde, and 10 mL isopropanol. Before the reaction, the reactor was purged with 1 MPa of hydrogen for 3 times to remove the air in the reactor, and then filled with 1 MPa of hydrogen pressure, the temperature was maintained at 60°C, and the reaction time was 2 h;

[0065] (2) After the reaction is completed, the reactor is placed in ice water and quickly cooled to room temperature, and the catalyst and reaction liquid are separated by centrifugation. The catalyst powder is filtered out and continuously rinsed with ethanol and then recycled for reuse. The filtrate is analyzed using a flame ionization detector (FID) of a gas chromatograph (GC) equipped with an HP-5 capillary column.

[0066] Example 6

[0067] This embodiment is different from Embodiment 5 in that the reaction time is 10 min, and the rest is the same as Embodiment 5.

[0068] Example 7

[0069] The difference between this embodiment and embodiment 5 is that the reaction time is 20 min, and the other aspects are the same as embodiment 5.

[0070] Example 8

[0071] The difference between this embodiment and embodiment 5 is that the reaction time is 30 min, and the other aspects are the same as embodiment 5.

[0072] Example 9

[0073] The difference between this embodiment and embodiment 5 is that the reaction time is 60 min, and the other aspects are the same as embodiment 5.

[0074] Example 10

[0075] The difference between this embodiment and embodiment 5 is that the reaction time is 150 min, and the other aspects are the same as embodiment 5.

[0076] Embodiment 11

[0077] This embodiment is different from Embodiment 5 in that the reaction pressure is 0.5 MPa, and the rest is the same as Embodiment 5.

[0078] Example 12

[0079] This embodiment is different from Embodiment 5 in that the reaction pressure is 2 MPa, and the rest is the same as Embodiment 5.

[0080] Embodiment 13

[0081] This embodiment is different from embodiment 5 in that the reaction temperature is 20°C, and the rest is the same as embodiment 5.

[0082] Embodiment 14

[0083] The difference between this embodiment and embodiment 5 is that the reaction temperature is 40° C., and the rest is the same as embodiment 5.

[0084] Embodiment 15

[0085] This embodiment is different from embodiment 5 in that the reaction temperature is 80° C., and the rest is the same as embodiment 5.

[0086] Example 16

[0087] The difference between this embodiment and embodiment 5 is that the reaction temperature is 100° C., and the rest is the same as embodiment 5.

[0088] Embodiment 17

[0089] The operation steps of this example are the same as those of Example 5. The catalyst obtained by centrifugation is washed with ethanol, and then placed in a vacuum oven at 80°C for 12 h for drying. A cycle experiment is also conducted under the same conditions. The catalyst is recycled for the second cycle to obtain the yield of benzyl alcohol product.

[0090] Embodiment 18

[0091] The operation steps of this embodiment are the same as those of embodiment 5, but the catalyst is recycled for the third time to obtain the yield of benzyl alcohol product.

[0092] Embodiment 19

[0093] The operating steps of this embodiment are the same as those of Example 5, but the catalyst is recycled for the fourth time to obtain a benzyl alcohol product yield.

[0094] Embodiment 20

[0095] The operating steps of this embodiment are the same as those of Example 5, but the catalyst is recycled for the fifth time to obtain a benzyl alcohol product yield.

[0096] Comparative Example 1-1

[0097] (1) Preparation of Au nanoparticles. Measure 150 mL of deionized water and place it in a beaker. The precursor of Au can be its metal precursor salt solution. Taking chloroauric acid as an example, take 1 g of HAuCl4 and dissolve it in 25 mL of deionized water to prepare an Au precursor solution (Au: 18.335 mg / mL) for later use. Take 491 μL of the Au precursor solution and add it to the beaker. Measure an appropriate amount of sodium citrate (the mass ratio of Au to sodium citrate is 1:5) and add it to the beaker. Stir at 1200 rpm for 1 min. Weigh 7.5 mg of sodium borohydride and dissolve it in 10 mL of ice deionized water. Use a 5 mL plastic dropper to quickly add the prepared sodium borohydride solution to the vigorously stirred Au precursor. The solution quickly changes from light yellow to wine red. Stir at 1200 rpm for 5 minutes and then turn off the stirring. Let it stand at room temperature for 1 hour. The prepared Au nanoparticles can be stored in a refrigerator at 4°C.

[0098] (2) Preparation of Au@Pt nanoparticles. The aqueous solution of Au nanoparticles prepared in step (1) was stirred at 1200 rpm. The precursor of Pt can be its metal precursor salt solution. Taking chloroplatinic acid as an example, 1 g of H2PtCl6 was dissolved in 50 mL of deionized water to prepare Pt for use. 1445 μL of Pt precursor solution was added to the aqueous solution of Au nanoparticles and stirred for 1 min. 20 mg of ascorbic acid was weighed and dissolved in 10 mL of deionized water. A 5 mL plastic dropper was used to add the prepared ascorbic acid solution to a beaker and stirred at 1200 rpm for 45 min to obtain an aqueous solution of Au@Pt nanoparticles. The prepared Au@Pt nanoparticles can be stored in a refrigerator at 4°C.

[0099] (3) Take 1980 mg of ZnO in a beaker, add 300 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain a carrier slurry.

[0100] (4) Loading Au@Pt onto ZnO. The ZnO slurry prepared in step (3) was stirred at 1200 rpm, and the Au@Pt nanoparticle solution prepared in step (2) was added dropwise into the ZnO slurry using a 5 mL plastic dropper and stirred for 1 h.

[0101] (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after the filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After the drying, it was sealed and stored.

[0102] The catalyst is named 1wt%Au@Pt / ZnO (m Au :m Pt =1:1.22)

[0103] Comparative Example 1-2

[0104] (1) Preparation of Au nanoparticles. Measure 150 mL of deionized water and place it in a beaker. The precursor of Au can be its metal precursor salt solution. Taking chloroauric acid as an example, take 1 g of HAuCl4 and dissolve it in 25 mL of deionized water to prepare an Au precursor solution (Au: 18.335 mg / mL) for later use. Take 491 μL of the Au precursor solution and add it to the beaker. Measure an appropriate amount of sodium citrate (the mass ratio of Au to sodium citrate is 1:5) and add it to the beaker. Stir at 1200 rpm for 1 min. Weigh 7.5 mg of sodium borohydride and dissolve it in 10 mL of ice deionized water. Use a 5 mL plastic dropper to quickly add the prepared sodium borohydride solution to the vigorously stirred Au precursor. The solution quickly changes from light yellow to wine red. Stir at 1200 rpm for 5 minutes and then turn off the stirring. Let it stand at room temperature for 1 hour. The prepared Au nanoparticles can be stored in a refrigerator at 4°C.

[0105] (2) Preparation of Au@Pt nanoparticles. The aqueous solution of Au nanoparticles prepared in step (1) was stirred at 1200 rpm. The precursor of Pt can be its metal precursor salt solution. Taking chloroplatinic acid as an example, 1 g of H2PtCl6 was dissolved in 50 mL of deionized water to prepare Pt for use. 1445 μL of Pt precursor solution was added to the aqueous solution of Au nanoparticles and stirred for 1 min. 20 mg of ascorbic acid was weighed and dissolved in 10 mL of deionized water. A 5 mL plastic dropper was used to add the prepared ascorbic acid solution to a beaker and stirred at 1200 rpm for 45 min to obtain an aqueous solution of Au@Pt nanoparticles. The prepared Au@Pt nanoparticles can be stored in a refrigerator at 4°C.

[0106] (3) Take 1980 mg of MgO in a beaker, add 300 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain a carrier slurry.

[0107] (4) Loading Au@Pt onto MgO. The MgO slurry prepared in step (3) was stirred at 1200 rpm, and the Au@Pt nanoparticle solution prepared in step (2) was added dropwise into the MgO slurry using a 5 mL plastic dropper and stirred for 1 h.

[0108] (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after the filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After the drying, it was sealed and stored.

[0109] The catalyst was named 1wt%Au@Pt / MgO (m Au:m Pt =1:1.22)

[0110] Comparative Examples 1-3

[0111] (1) Preparation of Au nanoparticles. Measure 150 mL of deionized water and place it in a beaker. The precursor of Au can be its metal precursor salt solution. Taking chloroauric acid as an example, take 1 g of HAuCl4 and dissolve it in 25 mL of deionized water to prepare an Au precursor solution (Au: 18.335 mg / mL) for later use. Take 491 μL of the Au precursor solution and add it to the beaker. Measure an appropriate amount of sodium citrate (the mass ratio of Au to sodium citrate is 1:5) and add it to the beaker. Stir at 1200 rpm for 1 min. Weigh 7.5 mg of sodium borohydride and dissolve it in 10 mL of ice deionized water. Use a 5 mL plastic dropper to quickly add the prepared sodium borohydride solution to the vigorously stirred Au precursor. The solution quickly changes from light yellow to wine red. Stir at 1200 rpm for 5 min and then turn off the stirring. Let it stand at room temperature for 1 hour. The prepared Au nanoparticles can be stored in a refrigerator at 4°C.

[0112] (2) Preparation of Au@Pt nanoparticles. The aqueous solution of Au nanoparticles prepared in step (1) was stirred at 1200 rpm. The precursor of Pt can be its metal precursor salt solution. Taking chloroplatinic acid as an example, 1 g of H2PtCl6 was dissolved in 50 mL of deionized water to prepare Pt for use. 1445 μL of Pt precursor solution was added to the aqueous solution of Au nanoparticles and stirred for 1 min. 20 mg of ascorbic acid was weighed and dissolved in 10 mL of deionized water. A 5 mL plastic dropper was used to add the prepared ascorbic acid solution to a beaker and stirred at 1200 rpm for 45 min to obtain an aqueous solution of Au@Pt nanoparticles. The prepared Au@Pt nanoparticles can be stored in a refrigerator at 4°C.

[0113] (3) Take 1980 mg of Al2O3 in a beaker, add 300 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain a carrier slurry.

[0114] (4) Loading Au@Pt onto Al2O3. The Al2O3 slurry prepared in step (3) was stirred at 1200 rpm, and the Au@Pt nanoparticle solution prepared in step (2) was added dropwise into the Al2O3 slurry using a 5 mL plastic dropper and stirred for 1 h.

[0115] (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after the filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After the drying, it was sealed and stored.

[0116] The catalyst was named 1wt%Au@Pt / Al2O3 (m Au :m Pt =1:1.22)

[0117] Comparative Examples 1-4

[0118] (1) The precursor of Au can be its metal precursor salt solution. Taking chloroauric acid as an example, 1 g of HAuCl4 is dissolved in 25 mL of deionized water to prepare Au precursor solution (Au: 18.335 mg / mL) for later use. The precursor of Pt can be its metal precursor salt solution. Taking chloroplatinic acid as an example, 1 g of H2PtCl6 is dissolved in 50 mL of deionized water to prepare Pt for later use.

[0119] (2) Weigh 495 mg of activated carbon and spread it evenly on a mortar. Take 361 μL of the Pt precursor solution, oscillate and sonicate it, then add 123 μL of the Au precursor solution and an appropriate amount of deionized water, sonicate for 5 min to mix them evenly, drop the mixed solution evenly onto the carrier, grind until the catalyst is fully impregnated, and dry it in a 70 °C drying oven for 12 h.

[0120] (3) The impregnated and dried catalyst was taken out and ground into uniform fine particles, and then loaded into a vertical tube furnace, with quartz wool placed above and below the catalyst bed. The temperature was raised from room temperature to 400°C at a heating rate of 5°C / min, and calcined at 400°C with nitrogen at 60 mL / min for 4 h, then cooled to 250°C and reduced with hydrogen at 40 mL / min for 1 h. After cooling to room temperature, the pipeline was purged with nitrogen, and the catalyst was taken out to obtain a 1wt% Au-Pt / C catalyst.

[0121] The catalyst was named as 1wt% Au-Pt / C (m Au :m Pt =1:1.22)

[0122] Comparative Example 2-1

[0123] The difference between this comparative example and Example 5 is that the reaction solvent is 10 mL of ethanol, and the rest is the same as Example 5.

[0124] Comparative Example 2-2

[0125] The difference between this comparative example and Example 5 is that the reaction solvent is 10 mL of methanol, and the rest is the same as Example 5.

[0126] Comparative Examples 2-3

[0127] The difference between this comparative example and Example 5 is that the reaction solvent is 10 mL 1,4-dioxane, and the rest is the same as Example 5.

[0128] Table 1 Activity test of Au@Pt / C catalysts with different Au / Pt mass ratios for hydrogenation of benzaldehyde to benzyl alcohol

[0129]

[0130] a The specific preparation method of the impregnation Pt / C catalyst is referenced in patent CN113999088B

[0131] According to the experimental results in Table 1, the benzaldehyde conversion rate of the Pt / C catalyst is 65.8%, and the benzyl alcohol selectivity is 80.4%. The benzaldehyde conversion rate of the Au-Pt / C catalyst with an alloy structure is 81.2%, and the benzyl alcohol selectivity is 72.1%. The incorporation of Au makes the catalyst show better activity. Compared with the Pt / C catalyst, the benzaldehyde conversion rate is increased by 15.4%, while the benzyl alcohol selectivity decreases by 8.3%. The catalyst 1wt%Au@Pt / C (m Au :m Pt =1:0.54) benzaldehyde conversion rate was 89.9%, benzyl alcohol selectivity was 94.1%; the catalyst Au@Pt / C (m Au :m Pt =1:2.07) benzaldehyde conversion rate was 97.4%, benzyl alcohol selectivity was 96.2%; the catalyst Au@Pt / C (m Au :m Pt =1:3) benzaldehyde conversion rate was 98.7%, benzyl alcohol selectivity was 87.6%; the catalyst Au@Pt / C (m Au :m Pt =1:1.22) benzaldehyde conversion rate is 99.9%, benzyl alcohol selectivity is 96.9%, catalytic performance is the best among the catalysts prepared in Examples 1-4, and compared with Pt / C prepared by impregnation method, benzyl alcohol yield is improved by more than 45%. In addition, the activity and selectivity of the catalyst with Au core Pt shell structure are better than those of Pt / C catalyst and Au-Pt / C catalyst with alloy structure.

[0132] Table 2 Effect of different carriers on the hydrogenation of benzaldehyde to benzyl alcohol

[0133]

[0134] According to Table 2, we investigated the effects of different supports. Since the support surface has abundant acid / base active sites and the ratio of acid / base active sites has a certain influence on the reaction selectivity, we selected several supports with different ratios of acid / base active sites to prepare catalysts. Basic oxide: ZnO; Amphoteric oxide: MgO, Al2O3。 When ZnO, MgO and Al2O3 were used as supports, the benzaldehyde conversion rate and benzyl alcohol selectivity did not exceed 90%, and the catalytic performance was not as good as that of the catalyst using activated carbon as a support. It may be due to the synergistic effect of metal-support that the catalytic performance decreased. The catalyst with activated carbon as a support had a benzaldehyde conversion rate of 99.9% and a benzyl alcohol selectivity of 96.9%, which was the best.

[0135] Through the above optimization of different bimetallic ratios and carriers, we selected the 1wt% Au@Pt catalyst of Example 2 as a catalyst for the hydrogenation of benzaldehyde to prepare benzyl alcohol, and investigated the effects of different conditions on catalytic activity and selectivity.

[0136] Table 3 Effect of reaction temperature on the preparation of benzyl alcohol by hydrogenation of benzaldehyde

[0137]

[0138] Table 3 shows the effect of reaction temperature on the conversion rate and selectivity of benzyl alcohol produced by hydrogenation of benzaldehyde. As the reaction temperature increases (20-100°C), the catalytic activity first increases and then stabilizes. The conversion rate of benzaldehyde increases from 88.8% to 99.9%. In addition, the selectivity of the target product benzyl alcohol first increases and then decreases. At 60°C, benzyl alcohol obtains the highest selectivity (96.9%). When the reaction temperature is increased from 60°C to 100°C, the conversion rate of benzaldehyde changes only slightly, indicating that benzaldehyde can be converted more stably under this temperature gradient. However, the selectivity of the target yield benzyl alcohol decreases by 3.6%, while the selectivity of the byproduct toluene increases by 2.9%, which may be due to the excessively high reaction temperature, which leads to the hydrogenation and deoxygenation of the carbon-oxygen bonds on benzaldehyde or benzyl alcohol, generating more toluene. Therefore, the optimal reaction temperature is 60°C, and the hydrogenation of benzaldehyde to prepare benzyl alcohol has the highest conversion rate and selectivity.

[0139] Table 4 Effect of different reaction solvents on the preparation of benzyl alcohol by hydrogenation of benzaldehyde

[0140]

[0141] Table 4 shows the effect of different reaction solvents on the conversion and selectivity of benzaldehyde. It can be seen from Table 4 that the highest conversion (99.9%) and selectivity (96.9%) are obtained when the solvent is isopropanol, followed by ethanol, which has a conversion of 69.5% and a selectivity of 72.7%, while the conversion (25.4%) and selectivity (26.6%) are lower when methanol is used as solvent. This may be because when the solvent is alcohol, the solubility of hydrogen in alcohol increases with the relative molecular mass of the alcohol, and at the same time, as the length of the alcohol chain increases, the electron density of the hydroxyl oxygen in the alcohol will have a stronger interaction with the catalyst surface. When the solvent is 1,4-dioxane, the reaction conversion rate is 54.2% and the selectivity is 69.9%, and the catalytic effect is not as good as isopropanol. Therefore, the best reaction solvent for the 1wt% Au@Pt / C catalyst in the hydrogenation of benzaldehyde to prepare benzyl alcohol is isopropanol.

[0142] Table 5 Effect of different hydrogen pressures on the preparation of benzyl alcohol by hydrogenation of benzaldehyde

[0143]

[0144] According to the results in Table 5, when the reaction was carried out under 0.5 MPa of hydrogen, the conversion of benzaldehyde was 89.5% and the selectivity of benzyl alcohol was 90.4%. As the hydrogen pressure reached 1 MPa, the conversion (99.9%) and selectivity (96.9%) of benzaldehyde reached the highest. As the hydrogen pressure further increased to 2 MPa, the conversion of benzaldehyde remained unchanged, and the selectivity of benzyl alcohol (92.1%) decreased slightly. Therefore, it can be concluded that the effective catalytic conversion of benzaldehyde to benzyl alcohol can be achieved under the initial hydrogen pressure of 1 MPa.

[0145] Table 6 Effect of reaction time on the preparation of benzyl alcohol by hydrogenation of benzaldehyde

[0146]

[0147] According to Table 6, as the reaction time increased from 10 min to 150 min, the benzaldehyde conversion rate gradually increased from 39.9% to 99.9% and then stabilized, and the benzyl alcohol selectivity gradually increased from 82.5% to 96.9% to reach a maximum value, and then decreased slightly. This may be due to the excessive reaction time causing the carbon-oxygen bond on the benzyl alcohol to be hydrodeoxygenated, resulting in more toluene. Therefore, the optimal reaction time for the hydrogenation of benzaldehyde to prepare benzyl alcohol is 120 min.

[0148] Table 7 1wt%Au@Pt / C (m Au :m Pt =1:1.22) Catalyst circulation experiment

[0149]

[0150] According to the catalyst cycle reaction results in Table 7, after 5 consecutive cycles, the benzaldehyde conversion rate decreased slightly from 99.9% to 94.4%, while the benzyl alcohol yield was still 90.0%. Au :m Pt =1:1.22) The catalyst has good reusability.

[0151] 1wt% Au@Pt / C (m Au :m Pt =1:1.22) Nanostructure and element distribution of the catalyst. Figure 1 It shows that 1wt% Au@Pt / C (m Au :m Pt =1:1.22) HAADF-STEM image of the catalyst and EDS element mapping of Au (red) and Pt (green). From the HAADF-STEM image, the nanoparticles are uniform in size and well dispersed. From the EDS element mapping, the nanoparticles have a clear Au core-Pt shell structure, confirming the formation of the Au@Pt core-shell structure.

[0152] According to the reaction results and related characterizations, a series of supported Au core-Pt shell nanostructured catalysts were prepared in the present invention and applied to the reaction of preparing benzyl alcohol by hydrogenation of benzaldehyde. By optimizing the reaction conditions, it was found that after the optimization, 1wt% Au@Pt / C (m Au :m Pt =1:1.22), isopropanol as a solvent, under the reaction conditions of 1 MPa hydrogen pressure and 60°C, a benzaldehyde conversion rate of 99.9% and a benzyl alcohol yield of 96.9% can be achieved. The catalyst has high activity and stability, the catalyst has high activity and stability, the reaction conditions are milder, the energy consumption is reduced to a certain extent, and it is more environmentally friendly. Therefore, the present invention has broad application prospects in industry.

[0153] The present invention is not limited to the specific technical solutions described in the above embodiments, and all technical solutions formed by equivalent replacement are within the protection scope required by the present invention.

Claims

1. A method for preparing benzyl alcohol by hydrogenating benzaldehyde using Au@Pt / C catalyst, characterized in that: The following steps are involved: (1) mixing a chloroauric acid solution with a sodium citrate aqueous solution and reducing it with a sodium borohydride aqueous solution to obtain Au nanoparticles; (2) mixing the chloroplatinic acid solution with the Au nanoparticles in step (1), and reducing them with ascorbic acid to obtain Au@Pt nanoparticles; wherein the mass ratio of the two metals Au:Pt is 1:1.22; (3) Adding activated carbon into deionized water and dispersing by stirring, and then subjecting to ultrasound to obtain activated carbon slurry; (4) Using activated carbon as a carrier, the activated carbon slurry in step (3) is mixed with the Au@Pt nanoparticles in step (2), and the obtained suspension is filtered and dried to prepare an Au@Pt / C catalyst; The total mass fraction of Au and Pt metals accounts for 1wt% of the catalyst; (5) Adding the reaction raw materials benzaldehyde, solvent and the Au@Pt / C catalyst of step (4) into a high-pressure reactor equipped with a thermal conductivity detector, and hydrogenating benzaldehyde to prepare benzyl alcohol under stirring; the initial hydrogen pressure is 1-2 MPa; the reaction temperature is 40-100°C; the reaction time is ≥2 h; the solvent is isopropanol; after the reaction, the catalyst and the reaction liquid are separated by centrifugation.

2. The method for preparing benzyl alcohol by hydrogenating benzaldehyde using Au@Pt / C catalyst according to claim 1, characterized in that: The amount of catalyst used in step (5) is based on a molar ratio of Pt to benzaldehyde of 1:1000.

3. The method for preparing benzyl alcohol by hydrogenating benzaldehyde using Au@Pt / C catalyst according to claim 1, characterized in that: (1) Preparation of Au nanoparticles: 150 mL of deionized water was placed in a beaker, a certain amount of Au precursor salt chloroauric acid was added to the beaker, an appropriate amount of sodium citrate was weighed and added to the beaker, and stirred at 1200 rpm for 1 min; a certain amount of sodium borohydride was weighed and dissolved in 10 mL of ice deionized water, and the prepared sodium borohydride solution was quickly added to the vigorously stirred Au precursor using a 5 mL plastic dropper. The solution quickly changed from light yellow to wine red. Stir at 1200 rpm for 5 minutes, then turn off the stirring and let stand at room temperature for 1 h. The prepared Au nanoparticles were stored in a refrigerator at 4°C. (2) Preparation of Au@Pt nanoparticles: The Au nanoparticle aqueous solution prepared in step (1) was stirred at 1200 rpm; a certain amount of Pt precursor salt chloroplatinic acid was added and stirred for 1 min; a certain amount of ascorbic acid was weighed and dissolved in 10 mL of deionized water, and the prepared ascorbic acid solution was added to a beaker using a 5 mL plastic dropper, and stirred at 1200 rpm for 45 min to obtain an Au@Pt nanoparticle aqueous solution. The prepared Au@Pt nanoparticles were stored in a refrigerator at 4°C. (3) Take a certain amount of activated carbon in a beaker, add 300 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain activated carbon slurry; (4) Loading Au@Pt onto activated carbon: Stir the activated carbon slurry prepared in step (3) at 1200 rpm, add the Au@Pt nanoparticle solution prepared in step (2) dropwise into the activated carbon slurry using a 5 mL plastic dropper, and stir for 1 h. (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after the filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After the drying was completed, the dish was sealed and stored; (6) Add the reaction materials, solvent and catalyst into a high-pressure reactor equipped with a thermal conductivity detector, and carry out catalytic hydrogenolysis reaction under stirring; before the reaction, purge the reactor with hydrogen several times to remove the air in the reactor.

4. The method for preparing benzyl alcohol by hydrogenating benzaldehyde using Au@Pt / C catalyst according to claim 3, characterized in that: The steps for preparing the catalyst are as follows: (1) Preparation of Au nanoparticles: Measure 150 mL of deionized water and place it in a beaker. Take 1 g of HAuCl4 and dissolve it in 25 mL of deionized water to prepare an Au precursor solution with Au: 18.335 mg / mL for later use. Take 491 μL of the Au precursor solution and add it to a beaker. Take an appropriate amount of sodium citrate with a mass ratio of Au to sodium citrate of 1:5 and add it to the beaker. Stir at 1200 rpm for 1 min. Weigh 7.5 mg of sodium borohydride and dissolve it in 10 mL of ice deionized water. Use a 5 mL plastic dropper to quickly add the prepared sodium borohydride solution to the vigorously stirred Au precursor. The solution quickly changes from light yellow to wine red. Stir at 1200 rpm for 5 minutes and then turn off the stirring. Let it stand at room temperature for 1 h. The prepared Au nanoparticles are stored in a refrigerator at 4°C. (2) Preparation of Au@Pt nanoparticles: The Au nanoparticle aqueous solution prepared in step (1) was stirred at 1200 rpm, 1 g of H2PtCl6 was dissolved in 50 mL of deionized water to prepare a Pt precursor solution, Pt: 7.61 mg / mL for later use; 1445 μL of the Pt precursor solution was added to the Au nanoparticle aqueous solution and stirred for 1 min; 20 mg of ascorbic acid was weighed and dissolved in 10 mL of deionized water, and the prepared ascorbic acid solution was added to a beaker using a 5 mL plastic dropper, and stirred at 1200 rpm for 45 min to obtain an Au@Pt nanoparticle aqueous solution. The prepared Au@Pt nanoparticles were stored in a refrigerator at 4°C. (3) Take 1980 mg of activated carbon in a beaker, add 300 mL of deionized water, stir at 1000 rpm for 1 min, and then ultrasonicate for 10 min to obtain activated carbon slurry; (4) Loading Au@Pt onto activated carbon: Stir the activated carbon slurry prepared in step (3) at 1200 rpm, add the Au@Pt nanoparticle solution prepared in step (2) dropwise into the activated carbon slurry using a 5 mL plastic dropper, and stir for 1 h. (5) The catalyst slurry collected in step (4) was filtered and washed with deionized water until the conductivity was 0. The solid obtained after filtration was placed in a petri dish and dried in a vacuum drying oven at 80°C for 12 h. After drying, the dish was sealed and stored. The catalyst was 1wt% Au@Pt / C m Au :m Pt =1:1.

22.

5. The method for preparing benzyl alcohol by hydrogenating benzaldehyde using Au@Pt / C catalyst according to claim 1, characterized in that: The reaction conditions in step (5) are as follows: an initial hydrogen pressure of 1 MPa, a reaction temperature of 60°C, and a reaction time of 2 h.

6. The method for preparing benzyl alcohol by hydrogenating benzaldehyde using Au@Pt / C catalyst according to claim 1, characterized in that: The mass of the catalyst added to the reactor in step (5) is 1 mmol benzaldehyde and 10 mL isopropanol, based on a molar ratio of Pt to benzaldehyde of 1:1000.

7. The method for preparing benzyl alcohol by hydrogenating benzaldehyde using Au@Pt / C catalyst according to claim 4, characterized in that: Using 1wt% Au@Pt / C m Au :m Pt =1:1.22 catalyzes the hydrogenation of benzaldehyde to prepare benzyl alcohol. The reaction is carried out at 1 MPa hydrogen pressure and 60°C for 120 min. The benzaldehyde conversion rate is 99.9% and the benzyl alcohol selectivity is 96.9%.

Citation Information

Patent Citations

  • A method for the selective catalytic conversion of 2-methylfuran to 1,4-pentanediol

    CN113999088B

  • Preparation method of microwave radiation enhancement alkali-modified carbon-supported noble metal catalyst for production of cinnamyl alcohol by means of selective hydrogenation

    CN109225209A

  • Platinum-nickel / activated carbon co-supported catalyst, and preparation method and application thereof

    CN109692687A

  • Preparation method and application of Pt-Au carbon-based in-situ reduction composite catalytic material

    CN111468091A

  • Catalytic hydrogenation of unsaturated aldehydes

    GB1123837A